Kraken reveals itself: the merger history of the Milky Way reconstructed with the E-MOSAICS simulations - Kruijssen, Diederik; Pfeffer, Joel L.; Chevance, Mélanie; Bonaca, Ana; Trujillo-Gomez, Sebastian; Bastian, Nate; Reina-Campos, Marta; Crain, Robert A.; Hughes, Meghan E. (Monthly notices of the Royal Astronomical Society, 2020)
Globular clusters (GCs) formed when the Milky Way experienced a phase of rapid assembly. We use the wealth of information contained in the Galactic GC population to quantify the properties of the satellite galaxies from which the Milky Way assembled.